CP violation in two-meson Tau decays induced by heavy new physics - Daniel A. López Aguilar; Javier Rendón; Pablo Roig (Journal of High Energy Physics)
Abstract We apply the effective field theory formalism that was used to study CP violation induced by heavy new physics in the τ → K S πν τ decays to the other two-meson tau decay channels. We focus on the rate and the forward-backward asymmetries, that are predicted using current bounds on the complex Wilson coefficients of the effective Lagrangian. We discuss our outcomes for the modes with (K/π)π 0 and KK S , that can be studied at Belle-II and a super-tau-charm facility. Our main finding is that current and forthcoming experiments would be sensitive to the maximum allowed CP rate asymmetry in the K ± K S modes if a precision of 5% is reached on this observable, that can check as well the BaBar anomaly in K S π. For the π ± π 0 channels, new physics would be difficult to probe at present. Disentangling new sources of CP violation would be most challenging in K ± π 0 and the other modes.